A porous copper complex and its preparation method and application

By developing porous copper complex [Cu6(ABTC)4(C2H6OS)2]n, the problem of fluorine-containing greenhouse gas recovery and separation in the prior art was solved, and efficient adsorption and separation of SF6 and NF3 gases were achieved, thereby reducing energy consumption.

CN119264159BActive Publication Date: 2025-02-25YANTAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411794844.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-25
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recover and separate fluorine-containing greenhouse gases, such as SF6 and NF3, and the traditional methods consume high energy and are complex in operation.

Method used

Develop a porous copper complex [Cu6(ABTC)4(C2H6OS)2]n, synthesized by copper salt and bis(3,5-dicarboxyphenyl)azo under specific conditions, forming high adsorption capacity and separation Properties of materials.

Benefits of technology

This porous copper complex has a high selective adsorption capacity for SF6 and NF3 gases, and can effectively separate SF6/N2 and NF3/N2 mixed gases, achieving efficient purification of the gas and reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264159B_ABST
    Figure CN119264159B_ABST
Patent Text Reader

Abstract

The invention discloses a porous copper complex and a preparation method and application thereof, and relates to the technical field of gas adsorption materials. The structural unit of the porous copper complex of the invention is [Cu6(ABTC)4(C2H6OS)2] n , where ABTC represents the anion structure obtained by removing the H on four ‑COOH from bis(3,5‑dicarboxyphenyl)azo, and n is a positive integer; the single crystal structure of the complex is a cage structure, P21 / c space group, and the unit cell parameters are a=23.6Å, b=18.4Å, c=31.8Å, α=90°, β=116°, and γ=90°. The porous copper complex of the present invention has good selective adsorption performance for SF6 gas small molecules, and can not only be used as a material for storing SF6 gas and NF3 gas, but also can be applied to the separation of SF6 / N2 gas and NF3 / N2 to achieve efficient purification of SF6 and NF3 gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas adsorption materials, and in particular to a porous copper complex and a preparation method and application thereof. Background Art

[0002] In the microelectronics industry, sulfur hexafluoride (SF6) is the most commonly used plasma etching gas, and nitrogen trifluoride (NF3) is also an excellent plasma etching gas. However, in the semiconductor device manufacturing process, only a few F-containing gases can be fully utilized, and most of them remain intact after the manufacturing process, resulting in a large amount of waste gas.

[0003] Currently, F-containing gases are mainly destroyed by combustion or thermal plasma decomposition. However, a small amount of F-containing gases is still released into the atmosphere. Most fluorinated greenhouse gases are extremely strong greenhouse gases that can persist in the atmosphere for a long time, and the gases can stay in the atmosphere for a long time. It is estimated that SF6 has a lifetime in the atmosphere of 3200 years and its greenhouse warming potential is 23900 times that of CO2; NF3 is second only to SF6 and its GWP is 17200 times that of carbon dioxide. Therefore, the emission of fluorinated greenhouse gases is strictly regulated.

[0004] For the industrial recovery of fluorinated greenhouse gases, cryogenic distillation, solution absorption, and membrane separation are the most commonly used methods, but these methods require high pressure and low temperature conditions. Traditional distillation is not only complex to operate, but also energy-intensive and requires a lot of energy; although fluorinated greenhouse gases and nitrogen can be separated based on membrane separation technology, they are hindered by the inherent low permeability of fluorinated greenhouse gases themselves. Therefore, new methods must be found to reduce energy consumption. Adsorbent-based pressure swing adsorption has significant advantages in gas separation, and the adsorbent used in this method should have high capacity and high selectivity.

[0005] Based on the above technical status, the present invention provides a porous copper complex and a preparation method and application thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a porous copper complex and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.

[0007] To achieve the above object, the present invention provides the following solutions:

[0008] One of the technical solutions of the present invention is to provide a porous copper complex, the structural unit of which is [Cu6(ABTC)4(C2H6OS)2] n , where ABTC represents the anion structure obtained by removing the H on four -COOH groups from bis(3,5-dicarboxyphenyl)azo, and n is a positive integer;

[0009] The single crystal structure of the complex is a cage structure, a P21 / c space group, and unit cell parameters are a=23.6Å, b=18.4Å, c=31.8Å, α=90°, β=116°, and γ=90°.

[0010] The second technical solution of the present invention is to provide a method for preparing the porous copper complex, comprising the following steps:

[0011] Copper salt and bis(3,5-dicarboxyphenyl)azo are added into a mixed aqueous solution of tetrafluoroboric acid, N,N-dimethylacetamide, dimethyl sulfoxide and ethanol at a molar ratio of 1:0.69, and the mixed system is reacted at a constant temperature of 70° C. for 3 days to obtain the porous copper complex.

[0012] As a further preferred embodiment of the present invention, the mixed volume concentration ratio of tetrafluoroboric acid, N,N-dimethylacetamide, dimethyl sulfoxide and ethanol is 1:30:20:10:10.

[0013] As a further preferred embodiment of the present invention, before the isothermal reaction, an ultrasonic dissolution step is also included.

[0014] The present invention constructs a three-dimensional structure with bis(3,5-dicarboxyphenyl)azo, and constructs a structural unit [Cu6(ABTC)4(C2H6OS)2] through the multiple coordination ability of the -COO group and the Cu(II) center. n The porous copper complex not only has a good adsorption capacity for small molecules of SF6 and NF3 gases, but also has a good separation effect on the currently difficult-to-separate SF6 / N2 mixed gas and NF3 / N2 components.

[0015] The pores of the bis(3,5-dicarboxyphenyl)azo ligand used in the present invention are suitable for the adsorption and separation of SF6.

[0016] The third technical solution of the present invention: providing the application of the above-mentioned porous copper complex in the adsorption of SF6 and / or NF3 gas.

[0017] Technical solution four of the present invention: Provide a method for the above-mentioned porous copper complex to adsorb SF6 and / or NF3 gas, comprising the following steps: in order to improve the separation performance of the complex for small gas molecules, immerse the porous copper complex in a low boiling point solvent, then perform vacuum degassing at 80°C to 100°C, and use the degassed porous copper complex for the adsorption of SF6 and / or NF3 gas.

[0018] In the present invention, the low boiling point solvent can be selected from methanol, dichloromethane or acetonitrile.

[0019] As a further preferred embodiment of the present invention, the soaking time in the low boiling point solvent is 2-3 days; more preferably, the low boiling point solvent is replaced 3-6 times a day.

[0020] As a further preference of the present invention, the vacuum degassing time is 10-12 hours.

[0021] The fifth technical solution of the present invention: providing the application of the above-mentioned porous copper complex in separating SF6 and N2 mixed gas or separating NF3 and N2 mixed gas.

[0022] Technical solution 6 of the present invention: Provide a method for separating a mixed gas of SF6 and N2 or a mixed gas of NF3 and N2 using the porous copper complex, comprising the following steps:

[0023] In order to improve the separation performance of the complex for small gas molecules, the porous copper complex is immersed in a low boiling point solvent and then vacuum degassed at 80°C to 100°C. The degassed porous copper complex is used for the adsorption of SF6 and / or NF3 gas.

[0024] In the present invention, the low boiling point solvent can be selected from methanol, dichloromethane or acetonitrile.

[0025] As a further preferred embodiment of the present invention, the soaking time in the low boiling point solvent is 1-2 days; more preferably, the low boiling point solvent is replaced 3-6 times a day.

[0026] As a further preferred embodiment of the present invention, the vacuum degassing time is 10 to 12 hours.

[0027] The present invention discloses the following technical effects:

[0028] The present invention uses metallic copper and bis(3,5-dicarboxyphenyl)azo, H4ABTC) ligand to synthesize a stable "cage-like" MOF-[Cu6(ABTC)4(C2H6OS)2] n This material has good selective adsorption performance for small molecules of SF6 gas. It can not only be used as a material for storing SF6 gas and NF3 gas, but also can be used for the separation of SF6 / N2 gas and NF3 / N2 to achieve efficient purification of SF6 and NF3 gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 It is a schematic structural diagram of the "pedal" type binuclear metal copper cluster inorganic secondary structural unit in the porous copper complex of the present invention.

[0031] Figure 2 It is a diagram of the connection mode between the ligand H4ABTC (bis(3,5-dicarboxyphenyl)azo) and binuclear copper in the porous copper complex of the present invention.

[0032] Figure 3 It is a three-dimensional structure diagram of the porous copper complex of the present invention.

[0033] Figure 4 This is the powder X-ray diffraction pattern of the porous copper complex prepared in Example 1 of the present invention.

[0034] Figure 5 It is the thermogravimetric diagram of the porous copper complex of the present invention.

[0035] Figure 6 3 is the N2 adsorption diagram of the porous copper complex prepared in Example 1 of the present invention at 77 K and 1 atm.

[0036] Figure 7 It is the SF6 and N2 gas small molecule adsorption diagram of the porous copper complex prepared in Example 1 of the present invention at 273 K, 298 K, and 1 atm.

[0037] Figure 8 It is the NF3 and N2 gas small molecule adsorption diagram of the porous copper complex prepared in Example 1 of the present invention at 273 K, 298 K, and 1 atm.

[0038] Fig. 9 This is the adsorption enthalpy diagram of the porous copper complex prepared in Example 1 of the present invention for SF6, NF3, and N2.

[0039] Fig.10 3 is a separation ratio diagram of the porous copper complex prepared in Example 1 of the present invention in a SF6 / N2 mixed gas at 298 K.

[0040] Fig.11 3 is a separation ratio diagram of the porous copper complex prepared in Example 1 of the present invention in a NF3 / N2 mixed gas at 298 K.

[0041] Fig.12 This is a separation diagram of the SF6 / N2 breakthrough curve of the porous copper complex prepared in Example 1 of the present invention at 298 K and 1 atm. DETAILED DESCRIPTION

[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0043] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0047] Example 1

[0048] To a 20 mL glass bottle, add copper nitrate trihydrate (0.025 g, 0.10 mmol) and H4ABTC (bis(3,5-dicarboxyphenyl)azo) (0.025 g, 0.069 mmol), and then add a mixture (7.1 mL) of tetrafluoroboric acid, N,N-dimethylacetamide, dimethyl sulfoxide, ethanol and water in a volume ratio of 0.1:3:2:1:1. Stir evenly, ultrasonicate at 360 W for 30 min, seal the glass bottle, and react at a constant temperature of 70 ° C for 3 days to obtain a complex (Cu-MOF).

[0049] The single crystal structure of the complex prepared in Example 1 belongs to a "cage structure", P21 / c space group, unit cell parameters are a=23.6 Å, b=18.4 Å, c=31.8 Å, α=90°, β=116°, γ=90°. The copper (II)-paddle wheel binuclear (Cu2(COO)4) unit is connected with the bis(3,5-dicarboxyphenyl)azo ligand to form a three-dimensional (3D) compound, and the copper atom is bridged with the four carboxyl groups of the ligand H4ABTC to form a "pedal" binuclear cluster ( Figure 1 ), the axial end of the binuclear cluster is coordinated by an oxygen atom in solvent water or a dimethyl sulfoxide molecule, and each bis(3,5-dicarboxyphenyl)azo is connected to four metal clusters ( Figure 2 ), the metal cluster is connected and expanded through bis(3,5-dicarboxyphenyl)azo ligands to form a three-dimensional porous structure ( Figure 3 ).

[0050] Figure 4 The powder X-ray diffraction pattern of the porous copper complex prepared in Example 1 of the present invention is shown in FIG. Figure 4 It can be seen that the powder X-ray diffraction curve of the obtained complex is consistent with the curve obtained by single crystal data simulation, indicating that the synthesized complex has good crystallinity and purity.

[0051] Example 2

[0052] The porous copper complex prepared in Example 1 is used to adsorb small gas molecules:

[0053] The porous copper complex was characterized by thermogravimetric analysis, and heating to 290°C kept the basic framework stable ( Figure 5 ), with good thermal stability. Soaked in acetonitrile for 2 days, during which the acetonitrile was replaced 3 times a day, and then vacuum degassed at 80°C for 12 hours, the adsorption of small molecular gases such as SF6, NF3, and N2 was tested using a Micromeritics 3-Flex gas adsorption instrument.

[0054] The N2 test temperature is 77 K, and the temperature is mainly controlled by liquid nitrogen. Through the N2 test, the BET and Langmuir specific surface areas of the complex are 1716m 2 / g and 2431 m 2 / g (see Figure 6 ).

[0055] The adsorption of N2, SF6, and NF3 at different temperatures is mainly achieved by reflux of ethanol in an external temperature control device, and the two temperatures of 273 K and 298 K are mainly tested. Under the conditions of 273 K and 1 atmosphere, the adsorption amounts of N2 and SF6 can reach 9.84 cm 3 / g, 186.61 cm 3 / g (see Figure 7 ), the adsorption amount of NF3 can reach 54.13 cm 3 / g (see Figure 8 ). Under 298K conditions, the adsorption amounts of N2, SF6, and NF3 can reach 6.58 cm 3 / g, 169.19 cm 3 / g, 31.65 cm 3 / g (see Figure 7 and 8 ).

[0056] In summary, under the conditions of 298K and one atmosphere, the adsorption capacity of the complex for small molecule SF6 is much greater than that for N2, followed by NF3, which means that the complex can be used as a storage material for SF6 gas and NF3 gas, and also has great potential for the separation of SF6 / N2 and NF3 / N2 mixed gases.

[0057] Adsorption enthalpy is an important parameter to measure the strength of the interaction between the adsorbent and the gas molecules during the adsorption process. It determines the energy required for gas desorption and the adsorption selectivity of various gases. In order to better understand the interaction between the complex and the gas, the isosteric adsorption heat (-Q st ) is used to illustrate. The Virial equation is used to fit the single-component gas isotherm adsorption curves at 273 K and 298 K to obtain the adsorption enthalpy (-Q st ).Depend on Fig. 9 It can be seen that the adsorption enthalpies of the complex for SF6, NF3 and N2 at the initial 0 atmosphere pressure are 19.1 kJ / mol, 15.6 kJ / mol and 11.9 kJ / mol respectively.

[0058] The adsorption isotherms of single-component gases and ideal adsorption solution theory (IAST) were used to simulate the separation of mixed gases under static conditions, and the Langmuir-Freundlich (LF) model was used to fit the adsorption isotherms to obtain relevant parameters. Fig.10 and 11 As shown in the figure, the fitting curves of each component gas at different temperatures are basically consistent with the experimental values, and the fitting R 2 The values ​​are all higher than 99.9%. At 298 K, the separation ratio of this complex for SF6 / N2 (10 / 90) can reach 276.5, and the separation ratio for NF3 / N2 (10 / 90) can reach 5.0.

[0059] Example 3

[0060] Application of porous copper complexes in separation of SF6 / N2 mixed gas:

[0061] In order to further evaluate the separation effect of the metal organic framework (MOF) on SF6 / N2 mixed gas and NF3 / N2 mixed gas under actual industrial conditions, a dynamic penetration experiment was carried out at 100 kPa and 298 K using a SF6 / N2 (or NF3 / N2) mixed gas (SF6 / N2, 1 / 9, v / v). 1 g of activated Cu-MOF was filled in the glass column, and the flow rate of the mixed gas was controlled by a mass flow controller. Before the experiment, 30 mL min -1 He was used for purging at room temperature, and then SF6 / N2 (10 / 90) mixed gas was sent into the fixed adsorption bed at a flow rate of 2mL / min, and the outlet mixed gas concentration was detected in real time by gas chromatograph. It can be seen that the penetration separation time can reach 120 min / g. In terms of material regeneration, high-purity helium was used for purging at room temperature, and then the next cycle experiment was prepared. After five cycles, the separation performance remained basically unchanged, indicating that it can be well regenerated and reused (see Fig.12 ).

[0062] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A porous copper complex, characterized in that: The structural unit is [Cu6(ABTC)4(C2H6OS)2] n , where ABTC represents the anion structure obtained by removing the H on four -COOH groups from bis(3,5-dicarboxyphenyl)azo, and n is a positive integer; The single crystal structure of the complex is a cage structure, a P21 / c space group, and unit cell parameters are a=23.6Å, b=18.4Å, c=31.8Å, α=90°, β=116°, and γ=90°.

2. The method for preparing the porous copper complex according to claim 1, characterized in that: The following steps are involved: Copper salt and bis(3,5-dicarboxyphenyl)azo are added into a mixed aqueous solution of tetrafluoroboric acid, N,N-dimethylacetamide, dimethyl sulfoxide and ethanol at a molar ratio of 1:0.69, and the mixed system is reacted at a constant temperature of 70° C. for 3 days to obtain the porous copper complex.

3. The preparation method according to claim 2, characterized in that: The mixed volume concentration ratio of tetrafluoroboric acid, N,N-dimethylacetamide, dimethyl sulfoxide and ethanol is 1:30:20:10:

10.

4. The preparation method according to claim 2, characterized in that: Before the isothermal reaction, an ultrasonic dissolution step is also included.

5. Use of the porous copper complex as claimed in claim 1 in adsorbing SF6 and / or NF3 gas.

6. A method for adsorbing SF6 and / or NF3 gas using the porous copper complex according to claim 1, characterized in that: The following steps are involved: The porous copper complex is immersed in a solvent, and then vacuum degassed at 80° C. to 100° C. The degassed porous copper complex is used for adsorption of SF6 and / or NF3 gas.

7. The method according to claim 6, characterized in that The vacuum degassing time is 10-12h.

8. Use of the porous copper complex as claimed in claim 1 in separating a mixed gas of SF6 and N2 or separating a mixed gas of NF3 and N2.

9. A method for separating a mixed gas of SF6 and N2 or a mixed gas of NF3 and N2 using the porous copper complex according to claim 1, characterized in that: The following steps are involved: The porous copper complex is immersed in a solvent, and then vacuum degassed at 80° C. to 100° C. The degassed porous copper complex is used for adsorption of SF6 and / or NF3 gas.

10. The method according to claim 9, characterized in that The vacuum degassing time is 10-12h.

Citation Information

Patent Citations

  • Porous copper complex, preparation method thereof and application of porous copper complex in SF6 adsorption and SF6 / N2 mixed gas separation

    CN116731336A

  • Porous cobalt complex with column-layer structure as well as preparation method and application of porous cobalt complex

    CN117986610A